IMPROVING WRITING DESCRIPTIVE SKILLS THROUGH SHORT DOCUMENTARY MOVIE AT ELEVENTH GRADE OF SMA 71, JAKARTA - Oktavia Abriwani (Dialectical Literature and Educational Journal, 2021)
This examination endeavors to work on understudies' accomplishment recorded as a hard copy elucidating text through short narrative film. This investigation was led by utilizing homeroom activity research. The subject of this investigation is class XI-B SMA 71 which comprised of 28 understudies. The examination was led in two cycles, cycle I comprised of two gatherings and cycle II comprised of two gatherings. The instruments of gathering the information were subjective information (meeting and perception sheet). In view of composing scores, understudies' score continued working on in each composing test. In direction test, the mean score was 58,86. In the trial of cycle I the mean score was 67,46 and the mean score in the trial of cycle II was 79,10.Based on the meeting and perception sheet it was tracked down that the understudies were intrigued, genuine, dynamic, roused, energetic recorded as a hard copy. The after effect of the examination showed that short narrative film essentially worked on understudies' accomplishment recorded as a hard copy spellbinding message.